Knowledge, attitudes, practices and oral health status in adolescents of the city of Córdoba, Argentina. - Fabiana Carletto-Körber; Carolina Isla; Laura Abrahim; Lila S. Cornejo (Journal of Oral Research, 2018)
Adolescence is a critical period in the appropriation of knowledge, attitudes and health practices. Objective: To analyze the experience of caries in relation to the level of knowledge, to attitudes and oral health practices in adolescents. Materials and methods: An analytical cross-sectional study was carried out in 52 adolescents attending the Provincial Dental Institute in the city of Córdoba, Argentina. The study included a clinical dental examination and a self-administered survey. All participating subjects provided an informed consent signed by their parents or guardians. The DMFT index and relative frequency of responses were calculated. Indices of "knowledge", "attitudes" and "practices" were created. Spearman's rank correlation coefficient between indices and a linear regression model with respect to the DMFT index were applied. Results: Mean age was 16.57±2.27 years. Female subjects accounted for 57.7% of participants. Between 92% and 96% of adolescents acknowledged that the presence of bacteria and a lack of oral hygiene could promote tooth decay. Ninety-six per cent reported using toothbrush and toothpaste, 32% reported using fluoride toothpaste, and only 19% used dental floss. The DMFT index was 4.7±4.0; component C 4.4±2.9. There was a significant correlation between the indices of knowledge and attitudes about oral health (p<0.05). The linear regression analysis showed as main predictors the questions: “Does brushing teeth prevent cavities?” And “How important is it for you to clean your teeth?” Conclusion: Although participants have information on some oral health care practices, it is necessary to design strategies that involve the participation of young people, with contents that take into account the interests and characteristics of the target population.